1982
DOI: 10.1073/pnas.79.18.5656
|View full text |Cite
|
Sign up to set email alerts
|

IgE immune complexes stimulate arachidonic acid release by mouse peritoneal macrophages.

Abstract: Resident mouse peritoneal macrophages were labeled with [3H]arachidonic acid and challenged with Sephadex beads coated with immune complexes of IgE and antigen. Arachidonic acid release by the cells was assessed by the quantity of radiolabel recovered from the culture medium. Freshly isolated macrophages responded to IgE immune complexes with a release of [3H]arachidonic acid that was linear for 1-2 hr. The magnitude of the response was dependent on both the number of immune complex-coated beads and on the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In our own experience and in other reports [12][13][14]19], a correlation exists between the levels of IgG anti-IgE and serum IgE in patients with high titers of serum IgE. How ever, no correlation was detectable between the level of IgG with auto-anti-IgE activity and the severity of disease.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In our own experience and in other reports [12][13][14]19], a correlation exists between the levels of IgG anti-IgE and serum IgE in patients with high titers of serum IgE. How ever, no correlation was detectable between the level of IgG with auto-anti-IgE activity and the severity of disease.…”
Section: Discussionsupporting
confidence: 60%
“…It has been reported that IgG anti-IgE autoantibody is specifically directed against the De2 region of IgE [2,3,[7][8][9], This autoantibody is believed to modulate a variety of immune functions [14][15][16][17] and/or possibly to interfere with the immunoassay of serum IgE [18,19], These find ings suggest additional mechanisms by which IgE could participate in an inflammatory response. This study exam ined the presence of IgG anti-IgE autoantibody in sera from patients with atopic diseases and the distribution of IgG subclasses with auto-anti-IgE activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although IgE interacts primarily with the Fc⑀R, there is evidence that it can also interact with the Fc␥R (43). Furthermore, IgE and IgG immune complexes have been shown to trigger a similar reaction from macrophages (44). Passive administration of 3E5 IgA and IgE to mice before C. neoformans infection resulted in prolonged survival extending a potential role in protection against fungal infection to these isotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Here we apply these techniques to a primary macrophage population, RPM, which has been extensively studied as a source of oxygenated 20:4 metabolites (10)(11)(12)(13)(14)(15)(16), and the RAW264.7 murine macrophage cell line (21), which is frequently used as a model for primary macrophages. The latter cells have been mainly studied with respect to alterations in the expression of genes relevant to the COX pathway (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%